P138 PREPERITONEAL ENDOSCOPIC GROIN HERNIA SURGERY - REASSESSMENT OF TOPOGRAPHIC ANATOMY AS A BASIS FOR STANDARDIZED DESCRIPTION OF SURGICAL STEPS. (25th November 2021) - Heimke, Marvin; Heinze, Tilmann; Kuthe, Andreas; Wedel, Thilo; Strey, Christoph W
Abstract: Aim: Fascial groin anatomy remains a conundrum. In particular, a clear anatomical allocation of the correct extraperitoneal dissection planes and spaces in total extraperitoneal endoscopic hernia surgery (TEP) has not yet agreed upon. The differing anatomical concepts are reflected by the variability of surgical approaches, the considerably long learning curves and subsequent complications. Thus, the aim of this study was to reassess the topographic anatomy of the groin region providing a basis to standardize the surgical steps of TEP according to clearly defined anatomical landmarks. Material and Methods: Video analysis of intraoperative surgical anatomy of groin hernia patients was correlated with the findings retrieved by macroscopic anatomical studies. The groin region of formalin fixed body donors was subjected to a stepwise dissection exposing the fascial system of the abdominal wall layer-by-layer and via different angles. Selected areas of interest were processed for histological study. Surgically relevant anatomical landmarks were defined and termed according to the most appropriate anatomical nomenclature. Results: The essential surgical dissection steps during TEP could be related to specific anatomical landmarks extending within the extraperitoneal space of the ventral and dorsolateral abdominal wall. The definition of fascial structures and interfaces and the identification of structures at risk allowed the identification of correct dissection planes for mesh placement. Conclusions: Our study helps to clarify the definition and nomenclature of anatomical key structures required for a standardized description of TEP in a simplified model. The data may contribute to reduce complications and improve surgical teaching and training.